2012
DOI: 10.1037/a0027895
|View full text |Cite
|
Sign up to set email alerts
|

Different processes for different therapies: Therapist actions, therapeutic bond, and outcome.

Abstract: Therapeutic bond, as a component of the alliance, is considered a common factor in psychotherapy; however, it may operate differently in various treatments. This article investigates therapist actions, particularly affect focus, in the formation of the bond and on reduction of symptoms in short-term dynamic psychotherapy (STDP) and cognitive therapy (CT) for cluster C patients. Forty-six cases (23 STDP and 23 CT) were assessed using the Psychotherapy Process Q-Sort, the Helping Alliance Questionnaire, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 69 publications
8
71
0
3
Order By: Relevance
“…For example, although the therapist alliance effect on outcome was not a consistent predictor of outcome across the analyses, it may be suggested, based on previous research (Marmarosh & Kivlighan, 2012), that the agreement between patient and therapist alliances has a consistent effect on outcome. Note further that although previous studies have demonstrated the importance of alliance in different treatment conditions and orientations, including supportive treatment (Horvath et al, 2011), in some cases supportive clinical management and psychotherapy may demonstrate different processes in which alliance is related to outcome (Ulvenes et al, 2012). …”
Section: Discussionmentioning
confidence: 98%
“…For example, although the therapist alliance effect on outcome was not a consistent predictor of outcome across the analyses, it may be suggested, based on previous research (Marmarosh & Kivlighan, 2012), that the agreement between patient and therapist alliances has a consistent effect on outcome. Note further that although previous studies have demonstrated the importance of alliance in different treatment conditions and orientations, including supportive treatment (Horvath et al, 2011), in some cases supportive clinical management and psychotherapy may demonstrate different processes in which alliance is related to outcome (Ulvenes et al, 2012). …”
Section: Discussionmentioning
confidence: 98%
“…Although the alliance is generally considered as a common factor, it may still operate differently in distinct treatment orientations (Ulvenes et al, 2012). Some theoretical orientations place greater emphasis on alliance as an active ingredient in treatment than others (Muran & Barber, 2010).…”
mentioning
confidence: 99%
“…In the same vein, one can now use neuroimaging to study the effects of treatment ingredients common to different therapy models, such as levels of adherence, therapeutic alliance or emotion activation [32,33]. Combined, such neuroimaging research may help clarify the relationships of treatment variables to both short- and long-term outcomes toward elucidating what works for whom.…”
Section: Discussionmentioning
confidence: 99%